Consecutive C1‐Homologation / Displacement Strategy for Converting Thiosulfonates into O, S‐Oxothioacetals. Issue 23 (6th October 2020) - Ielo, Laura; Pillari, Veronica; Miele, Margherita; Holzer, Wolfgang; Pace, Vittorio
Abstract: A conceptually intuitive synthesis of oxothioacetals is reported starting from thiosulfonates as electrophilic sulfur donors. The installation of a reactive CH2 Cl motif with a homologating carbenoid reagent, followed by the immediate nucleophilic displacement with alcoholic groups [(hetero)‐aromatic, aliphatic] offer a convenient access to the title compounds. Genuine chemoselectivity is uniformly observed in the case of multi‐functionalized systems. Abstract :